Association Between Prepregnancy Body Mass Index and Severe Maternal Morbidity. Issue 4 (April 2018) - Lisonkova, Sarka; Muraca, Giulia M.; Potts, Jayson; Liauw, Jessica; Chan, Wee-Shian; Skoll, Amanda; Lim, Kenneth I.
Abstract : (Abstracted from JAMA 2017;318(18):1777–1786) Several studies have shown that overweight and obesity are associated with adverse neonatal outcomes including preterm birth, severe congenital anomalies, and infant death. While some studies show an association between maternal obesity and pregnancy complications such as preeclampsia, thromboembolism, and cesarean delivery, less is known about the association between body mass index (BMI) and life-threatening maternal morbidity.